The Effects of Different Types of Environmental Noise on Academic Performance and Perceived Task Difficulty in Adolescents With ADHD. Issue 8 (June 2020) - Batho, Lauren P.; Martinussen, Rhonda; Wiener, Judith
Objective: To examine the effects of environmental noises (speech and white noise) relative to a no noise control condition on the performance and difficulty ratings of youth with ADHD ( N = 52) on academic tasks.Method: Reading performance was measured by an oral retell (reading accuracy) and the time spent reading. Writing performance was measured through the proportion of correct writing sequences (writing accuracy) and the total words written on an essay.Results: Participants in the white noise condition took less time to read the passage and wrote more words on the essay compared with participants in the other conditions, though white noise did not improve academic accuracy. The participants in the babble condition rated the tasks as most difficult.Conclusion: Although white noise appears to improve reading time and writing fluency, the findings suggest that white noise does not improve performance accuracy. Educational implications are discussed.